2000
DOI: 10.1063/1.1288789
|View full text |Cite
|
Sign up to set email alerts
|

The structure of deuterated methane–hydrate

Abstract: We present the results of a high-resolution neutron diffraction experiment with a fully deuterated methane hydrate type I at temperatures of 2, 100, and 150 K. Precise crystallographic parameters of the ice-like D2O lattice and the thermal parameters of the encaged methane molecules have been obtained. The parameters of the host lattice differ only slightly from values found for hydrates with asymmetric guests included, which leads to the conclusion that the host lattice of structure I is only a little adaptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
123
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(142 citation statements)
references
References 24 publications
16
123
1
2
Order By: Relevance
“…The free rotation of the methane molecules in the pure liquid and aqueous phases is corroborated by recent inelastic neutron scattering studies which showed that CH 4 molecules rotate almost freely in the cages of methane hydrates. 24 Our ACF results can also be compared with the values reported by Laaksonen and Stilbs. 20 It must be noted that in their study the conditions are slightly different: water and methane are modeled by the earlier TIP4P and united-atom OPLS potentials, respectively, and the aqueous solutions of methane are more concentrated ͑they contain four methane particles per simulation box͒.…”
Section: B Molecular Dynamics Simulationsmentioning
confidence: 57%
“…The free rotation of the methane molecules in the pure liquid and aqueous phases is corroborated by recent inelastic neutron scattering studies which showed that CH 4 molecules rotate almost freely in the cages of methane hydrates. 24 Our ACF results can also be compared with the values reported by Laaksonen and Stilbs. 20 It must be noted that in their study the conditions are slightly different: water and methane are modeled by the earlier TIP4P and united-atom OPLS potentials, respectively, and the aqueous solutions of methane are more concentrated ͑they contain four methane particles per simulation box͒.…”
Section: B Molecular Dynamics Simulationsmentioning
confidence: 57%
“…Under these conditions, new XRPD peaks suddenly appeared (in o10 min), corresponding to the sI structure of the methane hydrate [27][28][29] . The formation process was completed in 30 min, and peak intensities did not change when continuing the process for another 30 min.…”
Section: Resultsmentioning
confidence: 99%
“…Under these conditions, natural hydrates crystallize in a cubic structure known as type sI. This structure is constituted by cages of two different types: (i) six large cages having 12 pentagonal and 2 hexagonal faces (denoted by 5 12 6 2 ) formed by 24 water molecules and (ii) two small cages having 12 pentagonal faces (denoted by 5 12 ) formed by 20 water molecules 2 . These cages have an average cavity radius of 0.433 and 0.395 nm, respectively, which is enough to host one methane molecule per cage, resulting in a nominal stoichiometry 1CH 4 Á 5.75 H 2 O.…”
mentioning
confidence: 99%
“…The molecular structures of various water cages ( Figure 2) are obtained from the crystalline structures of sI, 57 sII, 58 sH, 59 and sK. 7 To obtain a likely most stable structure of the empty water cage, we adjusted the arrangement of the hydrogen atoms to minimize the number of the nearest neighbor pairs that both have a dangling H-bond as in Refs.…”
Section: Computational Detailsmentioning
confidence: 99%